(untitled) (The Journal of Geography Education in Africa, 2022)
The Zimbabwean education system that was inherited from the days when Zimbabwe was still Rhodesia provided strong content knowledge at the expense of critical skills and competencies. In its curriculum framework of 2015–2022, the government of Zimbabwe noted that mastery of subject content was inadequate for the schooling system needed by the country (Government of Zimbabwe, 2015). In response, it explained, it had developed a curriculum framework based on the introduction of competency-based continuous assessments in schools. The purpose of this article is to explore the system of competency-based continuous assessment learning activities (CBCALA) that is being adopted in the assessment of Geography at Ordinary Level in secondary schools. Further to that, it aims to determine the challenges that Geography teachers face in the implementation of CBCALA. The study at the heart of the article is based on the social constructivism of Vygotsky (1978); and on the philosophy of ubuntu, which is widely espoused throughout southern Africa and further north on the continent. An interpretive research paradigm was adopted for a case study carried out in Mutare District in Zimbabwe. Data were generated through purposive sampling of the participants and were analysed by generating thick descriptions and themes. The study revealed the need for geography teachers to develop CBCALA through the formulation of clearly stated problems and through the assessment of well-formulated objectives that assess learners’ academic knowledge and competencies. This is achieved by developing research-based and practically oriented tasks. Geography CBCALA should be learner-centred, using both individualised and group assessment tasks. A marking guide is critical for use in marking the assessment tasks. Several challenges that impede the implementation of CBCALA include time constraints, the inadequate training teachers receive on the use of CBCALA, large classes, increased workload and inadequate equipment. The study recommends reviewing the quantity of content coverage; computerising the documentation of assessment tasks and student records; recruiting more teachers; and mobilising resources from within the community.